LITERATURE REVIEW OF THE MAIN MICROBIAL MARKERS FOR DIAGNOSIS OF COLORECTAL CANCER - Bueno Carneiro, Eduardo; Cesar da Silva, Junio; Souza da Silva, Jonas; Marcon Henke, Juliana; Iacer Bueno, Anderson (Health and Society, 2023)
The objective of the present work is to promote a review of the main microbial markers for detection of colorectal cancer (CRC), as well as to explain the difficulties involved in their standardization. Several studies show the elevation of certain microorganisms to the detriment of the intestinal microbiome during the development of CRC and one of the reasons that favor them are virulence factors. Streptococcus galollyticus subs. gallolyticus and Clostridium symbosium are among the main microbial markers. However, isolates do not demonstrate the ideal sensitivity and specificity for CCR detection, and the result is optimized by associating some markers with the usual ones, such as human fecal hemoglobin (F-HB). These markers are promising, however, there is a need for further studies for their standardization.